Polyomavirus interaction with the DNA damage response - Justice, Joshua L. (Virol Sin, 2015)
Viruses are obligate intracellular parasites that subvert cellular metabolism and pathways to mediate their own replication—normally at the expense of the host cell. Polyomaviruses are a group of small DNA viruses, which have long been studied as a model for eukaryotic DNA replication. Polyomaviruses manipulate host replication proteins, as well as proteins involved in DNA maintenance and repair, to serve as essential cofactors for productive infection. Moreover, evidence suggests that polyomavirus infection poses a unique genotoxic threat to the host cell. In response to any source of DNA damage, cells must initiate an effective DNA damage response (DDR) to maintain genomic integrity, wherein two protein kinases, ataxia telangiectasia mutated (ATM) and ATM- and Rad3-related (ATR), are major regulators of DNA damage recognition and repair. Recent investigation suggests that these essential DDR proteins are required for productive polyomavirus infection. This review will focus on polyomaviruses and their interaction with ATM- and ATR-mediated DNA damage responses and the effect of this interaction on host genomic stability.